Historicizing National Socialism and Mehmet Genç - Ahmet Okumuş (İstanbul İktisat Dergisi)
National Socialism, more than just a political ideology, signifies one of the most convoluted historical events of the twentieth century. The depiction of the Nazi era in post-war historiography emerged as a contentious realm of debate. Distinct interpretative divides crystallized: on one side, the ‘Sonderweg’ theories asserting Germany’s unique modernization journey, and on the other, perspectives anchoring events to the prevailing geopolitical dynamics and broader factors of the period. Germany’s assertive strides under National Socialist leadership, especially during the 1930s, amplified the challenges of a nuanced treatment of the topic. In Turkey, amidst a landscape of contending modernization narratives, National Socialism had resonated with those seeking a more culturally attuned renewal. This study aims to scrutinize the Ottoman economic historian Mehmet Genç’s evaluation of National Socialism. Genç’s engagement with the subject goes beyond mere historical processes and political events, encompassing the philosophical background of National Socialism. The analysis will first delve into Genç’s evaluation of National Socialism through the lens of the Sonderweg theses, then explore the foundational philosophical orientations that underpin Genç’s academic perspectives and methodologies..